2020
DOI: 10.18203/2349-2902.isj20204118
|View full text |Cite
|
Sign up to set email alerts
|

Compare outcome in patients of ileostomy and colostomy closure with surgical stapler versus ileostomy and colostomy closure with hand sewn anastomosis: a prospective study

Abstract: Background: Diverting temporary stoma is created to protect the primary bowel pathology and distal anastomosis. Once that primary pathology has been overcome or distal anastomosis gets healed, closure of temporary stomas can be carried out. Invention of stapling devices for intestinal anastomosis provided another dimension than hand sewn method to the stoma closure techniques. In this study, we have compared two methods of loop stoma closure-hand sewn method versus stapler method.Methods: This is prospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…To this date, there have been many prospective, randomized trials that have demonstrated no significant differences between stapled and handsewn anastomoses in terms of anastomotic leak rate, length of hospital stay, or overall morbidity. 8 Both prospective studies 9 and meta-analysis 10 have demonstrated no significant difference in leak rate between stapled and handsewn technique for elective ileostomy and colostomy closure procedures. The same findings has been demonstrated for emergent anastomoses in multiple prospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…To this date, there have been many prospective, randomized trials that have demonstrated no significant differences between stapled and handsewn anastomoses in terms of anastomotic leak rate, length of hospital stay, or overall morbidity. 8 Both prospective studies 9 and meta-analysis 10 have demonstrated no significant difference in leak rate between stapled and handsewn technique for elective ileostomy and colostomy closure procedures. The same findings has been demonstrated for emergent anastomoses in multiple prospective studies.…”
Section: Introductionmentioning
confidence: 99%